Potential of Neem Leaves on Preservation of Selected Elemental Compositions in Two Tomato Cultivars from Sokoto, Nigeria - Abdulrahman Hamza; Abubakar Mohammad Gumi; Adamu Aliyu Aliero; Aminu Umar Imam; Yusuf Sarkingobir; Umar Tambari (BIORE Scientia Publisher, 2023)
The aim of this study is to determine the effect of neem leaves in preserving the mineral elements content of two tomato types from Sokoto state, Nigeria. Healthy, ripe and firm tomato fruits brought from Sokoto City, were selected, cleaned for this study. 5%, 10% and 25% by were prepared by dissolving respective 5g, 10g and 25g neem extracts in 9.5, 9.0 and 7.5 liters of distilled water respectively to preserve tomatoes. The experiment was laid in a completely randomized design. And elements, Na, K, Ca, Mg, and P were determined in the tomatoes after the experiment using atomic absorption spectroscopy. The levels of Na, K, Ca, and P in Daneka after preservation ranges are: 1.1-1.3(ppm), 2.1-2.3 (ppm), 1.0-1.3 (ppm), 0.30-0.34 (ppm), and 0.3200-0.3330 (ppm) respectively. The levels of Na, K, Ca, and P in UTC after preservation ranges are: 1.6-1.10 (ppm), 1.6-1.10 (ppm), 0.10-1.16 (ppm), 0.30-0.35 (ppm), and 0.9997-1.0998 (ppm) respectively; revealing an increasing trend of elemental contents of all the tomato cultivars with an increasing neem concentration. Thus, the neem leaves indicate the capacity to preserve a typical quality parameter of tomatoes, that is concentration of Na, K, Ca, and P elements at p < 0.05 significant level.